Biblometric Analysis of the Effect of Type II Diabetes Mellitus on Immunity - Husnia, Attahiyatul; Ramadhan, Bintang Fadhil; Yuniarti, Elsa (Jurnal Biologi Tropis, 2025)
Type 2 diabetes mellitus is the inability of the body's cells to respond to insulin or so-called insulin resistance which causes hyperglycemia. The body's immune system is a complex system that functions to protect the body from various diseases and infections. This research was conducted with the aim of applying bibliometric methods using quantitative analysis to trace the development of research related to type 2 Diabetes Mellitus. This study uses a biblometric analysis method that can help researchers in studying the content of bibliography, citation analysis of each article taken from the lens database. The results of data with the keywords DM type 2, immune, and complication are not too much, only about 475 data were obtained, and after being identified and cleaned using vosviewer, data was obtained in the form of several clusters such as images.